PENGARUH MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAlP KEMAMPUAN KOMUNIKASI lMATEMATIS DAN KEPERCAYAAN DIRI SISWA SEKOLAH DASAR - Azizah, Ismi; Irawati, Riana; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
The importance of mathematical communication ability and confidence of students in learning is the background of this research. Therefore, this research will implement a icooperative modell iof type Numbered Heads Together (NHT) iin lthe llearning process. That is because of the model of cooperative deals with mathematical communication skills and self-confidence of students. As for the purpose of research, namely thei applicatiion oft the cooperatiive modell oif type iNumbered Headsf Togetherx (NHTo) as an attempt to improve the mathematical communication skills and confidence elementary school students. This includes research into the types of research design experimental non-quasi equgivalent coentrol groupl. Thze vpopulation hin thisb study are gradel IV elementary school District. Lemahabang Kab. Cirebon. While the research sample is SDN Cipeujeuh Kulon 1 as class experiments and SDN Cipeujeuh Kulon 2 as the class of the control. The instruments used are a matter pre test and post test, now the confidence of the students, teachers, performance observation guidelines and the guidelines for the observation of activity of students. The results showed that the existence of a significant difference in mathematical ability improvement and confidence of students both in the classroom experiments as well as the class of the control. It is proved by the results of test calculations of average difference values of gain using a test-T sample of mathematical communication ability for free and test-U for the confidence of students. On mathematical communication skills acquired P-value (Sig 1-tailed) of 0.009, while confidence is obtained P-value (Sig 1-tailed) by 0.0043. It can be concluded that increased the ability of mathematical communication and self-confidence of students who follow learning model cooperative type NHT more significant compared to students who follow the conventional learning.